Strengthening the nuclear nonproliferation regime - Lettow, Paul Vorbeck, 1977- (CSR (New York, N.Y.), 2010)
Nuclear technology has long been recognized as capable of both tremendous benefits and tremendous destruction. With this in mind, countries have devised international arrangements intended to promote peaceful nuclear applications while preventing the spread of materials, equipment, and technologies useful for producing nuclear weapons. Today, however, it is clear that this global nonproliferation regime is falling short. North Korea withdrew from the Nuclear Nonproliferation Treaty (NPT) in 2003 and has since tested two nuclear devices. Iran, while still a party to the NPT, has developed the capacity to enrich significant amounts of uranium; many believe it is seeking to build nuclear weapons or at least attain the ability to do so. In addition, there is the challenge of facilitating the expansion of nuclear energy, something that could help reduce carbon emissions, while preventing countries from using related technologies for military purposes. Finally, the prevalence of nuclear materials only intensifies the fear that terrorist groups could acquire them through theft or a deliberate transfer from a state. In this Council Special Report, Paul Lettow examines the shortcomings of the nonproliferation regime and proposes a comprehensive agenda to shore it up.